Effect of sodium 2,3-dimercaptopropane-1-sulphonate (DMPS) on chronic daunorubicin toxicity in rabbits: comparison with dexrazoxane - Hrdina, Radomír; Gersl, Vladimír; Klimtová, Ivona; Simůnek, Tomás; Mazurová, Yvona; Machácková, Jarmila; Adamcová, Michaela (Acta medica (Hradec Kralove), 2002)
A possible protective action of DMPS (a dithiol chelating agent) against chronic daunorubicin toxicity in rabbits in comparison with dexrazoxane was investigated. The rabbits were divided into five groups: control (saline, 1 ml/kg i.v.), daunorubicin (3 mg/kg i.v.), DMPS (50 mg/kg i.v.); the remaining two groups were pre-treated either with dexrazoxane (60 mg/kg i.p.) or DMPS (50 mg/kg i.v.) 30 min before administration of daunorubicin (3 mg/kg i.v.). Drugs were given once a week for 10 weeks. Routine biochemical parameters were determined in weeks 1, 5 and 11. In the 11th week, invasive haemodynamic parameters were measured, then the rabbits underwent autopsy, cardiac tissue was examined by light microscopy and scored semiquantitatively. The contents of calcium, potassium, magnesium, iron and selenium were measured in the left heart ventricle. DMPS administered alone was well tolerated and did not cause any major signs of toxicity. It decreased the cardiac content of calcium, but did not affect the iron concentration. In contrast to dexrazoxane, DMPS pre-treatment did not prevent the decline in body weight in weeks 8-11 caused by daunorubicin, actually worsened mortality (26.7% vs 40.0%), did not ameliorate daunorubicin-induced nephrotic syndrome, and did not prevent the occurrence of the severe myocardial lesions. Unlike dexrazoxane, a lack of protective effect of DMPS against chronic daunorubicin toxicity in rabbits was demonstrated. The underlying cause may consist in the fact that DMPS does not efficiently chelate tissue iron and thus may not prevent the formation of oxygen free radicals.
Keywords: razoxan; vápník; mužské pohlaví; chelátory; daunomycin; železo; Calcium; Iron; Unithiol; myokard; zvířata; unithiol; králíci; Antibiotics, Antineoplastic; Myocardium; Daunorubicin; Rabbits; Heart; Razoxane; Chelating Agents; protinádorová antibiotika; srdce; Male; Animals